(untitled) (Journal of Contemporary Studies, 2025)
1. Nuclear Arms Control in South Asia Politics, Postures, & Practices 2. Kashmir: The Unfinished Agenda of Partition 3. Rethinking International Political Economy 4. Geopolitics and Democracy: The Western Liberal Order from Foundation to Fracture